The Relationship between Self-Efficiency and Mathematical Knowledge of 3-D Shapes of Fifth Grade of Elementary School - Nurul Faradilla; Zetra Hainul Putra; Eddy Noviana (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2022)
This study aims to determine the relationship between self-efficacy and mathematical knowledge of 3-D shapes of fifth graders of elementary school. Participants in this study were 76 fifth grade students from a public school in Duri region, Indonesia. The method used in this research is the correlation and regression study. Instruments in this study are non-test and test. The non-test instrument is in the form of a questionnaire, and the test instrument is in the form of questions regarding the 3-D shapes. The indicators of self-efficacy consist of magnitude (level of task difficulty), strength (strength of belief) and generality, while the indicators of mathematical knowledge of 3-D shapes are properties, area, and volume of cubes and rectangular prism. The data analysis technique was carried out by presenting data, normality test, linearity test, linear regression test, and hypothesis testing using Pearson's product moment correlation. The results show that there is a significant positive relationship between students’ self-efficacy and mathematical knowledge of 3-D shapes.